MENTAL DISABILITY AND CRIMINAL JUSTICE IN INDONESIA: A LEGAL AND INFORMATIONAL LITERACY APPROACH BASED ON MAQASHID AL-SYARI’AH. - Nasution, Jumanah; Nasution, Muhammad Syukri Albani; Siregar, Ramadhan Syahmedi (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
This study explores the concept and practice of criminal responsibility for individuals with mental disabilities in Indonesia through an interdisciplinary lens that integrates doctrinal legal analysis, information literacy, and Islamic legal principles, particularly Maqashid al-Syariah. The research aims to (1) examine the legal construction of criminal liability for people with mental disabilities under Indonesian law, (2) assess the role of information literacy in legal processes involving such individuals, and (3) analyze the alignment of Indonesian legal practices with Islamic principles of justice, proportionality, and human dignity. Employing a normative legal research method, this study utilizes statute, case, and comparative approaches to analyze laws, court decisions, and scholarly interpretations. The findings reveal persistent inconsistencies in how courts assess mental incapacity, often relying on inadequate psychiatric evaluations and failing to apply protections guaranteed by Law No. 8 of 2016 and the revised Criminal Code (KUHP Articles 38–39). Additionally, the study highlights a significant gap in information literacy among legal actors and affected families, exacerbating procedural injustice. The case of a schizophrenic defendant in South Sulawesi illustrates how the lack of accessible legal information and contextual assessment leads to human rights violations. The research concludes that integrating Maqashid al-Syariah—particularly the principle of hifz al-‘aql (preservation of intellect)—with enhanced information literacy frameworks offers a more just, inclusive, and humane approach to criminal responsibility. Legal reform, public legal education, and individualized assessment are critical to ensuring that the rights and dignity of mentally disabled individuals are upheld within Indonesia’s justice system.